EFFECT OF FLUORIDE-RELEASING MATERIALS ON THE PREVENTION OF ENAMEL EROSION: A MICROHARDNESS AND SCANNING ELECTRON MICROSCOPIC EVALUATION - Meral, Ece; Dursun, Meltem Nermin; oz, Alperen; Ergin, Esra (Int Soc Fluoride Research, 2021)
The aim of the study was to evaluate the preventive effect of different bioactive restorative materials on the neighbouring enamel under erosive conditions. Fifty-two intact human incisors were collected. Standard Class V cavities were prepared and the specimens were randomly divided into 4 groups (n=13) according to the restorative materials used: (i) control group: composite resin (CR) group (Harmonize/KERR), (ii) resin modified glass ionomer (RMGIC) group (RivaLight Cure/SDI), (iii) glass carbomer (GC) group (GlassFill/GCP-Dental), and (iv) high viscosity glass ionomer (HVGIC) group (EQUIA/GC). After polishing with aluminum oxide discs, the microhardness values of the restorative materials and the neighbouring enamel were measured with a Vickers hardness device. The specimens were then subjected to an erosive procedure. The final microhardness measurements were performed and the data were subjected to statistical analysis. The surface topographies of the specimens from each group were evaluated, before and after erosive challenge, with a scanning electron microscope (SEM). Significant decreases were observed in the microhardness values of the neighbouring enamel for all the materials after the erosive challenge when compared to the baseline. However, the decreases in the microhardness of the neighbouring enamel were significantly lower in the GC and HVGIC groups than in the RMGIC and CR groups. The SEM findings were in accordance with the microhardness test results. The bioactive HVGIC and GC materials might be better tooth-colored restoration options for preventing neighbouring enamel demineralization in patients who are at risk of dental erosion.
Keywords: Bioactive materials; Dental erosion; Fluoride release; Minimal invasive dentistry; Remineralization